SOSIALISASI MANAJEMEN PRE MENSTRUAL SYNDROME PADA REMAJA PUTRI DI SMPIT DAN SMAIT ANAK SHOLEH MATARAM - Ni Made Amelia Ratnata Dewi; Candra Eka Puspitasari (Universitas Mataram, 2022)
Menstruation is a physiological phenomenon experienced by women, most women report experiencing symptoms of premenstrual syndrome (PMS) in the form of breast pain, flatulence, nausea, headaches and emotional changes. These PMS symptoms can reduce the quality of health, interfere with learning concentration as well as achievement and active learning activities, especially for young women who attend school. Management (PMS) can be done non-pharmacologically (without drugs) or pharmacologically (with drugs) if there are persistent symptoms so it is necessary to make socialization about PMS management for young women. The purpose of this community service activity is to organize a socialization so that young women can understand PMS management. The method of socialization carried out is by way of presentation of material by resource persons, discussions and questions and answers as well as distribution of brochures. The socialization activities were carried out at SMPIT and SMAIT Anak Sholeh Mataram. A total of 20 students participated in the socialization activity. Activities carried out well. The mean value of the pretest obtained is 7.3. After the exposure there was an increase in the post test score to 9.4. The results of the discussion and question and answer show that many students have PMS problems, especially with symptoms of pain. Pain management can be done independently by buying analgesics (pain relievers) which are sold at pharmacies or licensed drug stores with parental supervision. After the socialization, there was an increase in the pretest and posttest scores. This service activity is one of the health promotions for the community and must be held regularly.